Children and safety in Australian policy: Implications for organisations and practitioners. Issue 1 (5th October 2020) - Powell, Mary Ann; Graham, Anne; Canosa, Antonia; Anderson, Donnah; Taylor, Nicola; Robinson, Sally; Moore, Tim; Thomas, Nigel Patrick
Abstract: Child safety is now a national policy priority in Australia. Extensive enquiries and reviews have escalated legislative and policy responses focused on developing, maintaining and monitoring "child safe" organisations. The recommendations of the Royal Commission into Institutional Responses to Child Sexual Abuse point to the importance of cultural conditions within organisations in supporting child safety and the need for responsive change in some organisations. Drawing on a recent policy analysis, undertaken as part of a larger Australian Research Council Discovery Project, this article examines how children and safety are constructed, within and across relevant state and federal government policies in Australia, and the implications of this. Distinctions are drawn between conceptualisations of children within the broader education policy context and two specific policy contexts in which children are considered particularly vulnerable to abuse – out‐of‐home care and disability. The findings indicate that policy discourses of "child safe" potentially foster different emphases and approaches in organisations. These have implications for the way children are positioned in relation to their safety, how their rights are recognised and implemented, and what is required to foster cultural conditions within organisations to best support children's safety and wellbeing.